Do Servant Teachers Practice What They Preach? A Case of Academic Servant Leadership in A Faith-Based School in Indonesia - Natha Bella Angella; Ricky Ricky (Petra International Journal of Business Studies, 2022)
Servant Leadership has been considered as significant to improve the leadership of educational leaders including the one at schools. This research explores the academic leadership in a faith based Senior Highschool in Indonesia. The research involves a mix method of interview and questionnaire survey with the purpose of confirming the understanding and enactment of servant leadership by the teachers. This study was guided by the central question ‘To what extent the teachers understand Servant Leadership? To what extent the teachers have practiced Servant Leadership (SL)?’ for interviewing the teachers. The authors apply the Servant Leadership Behavior Scale as the theoretical foundation and statement items for 261 students. The collected data are then processed using qualitative data analysis which involves a reiterative process of data display, data condensation and conclusion drawing. The authors concluded that teachers understand Servant Leadership as ‘mengutamakan orang lain’ (prioritizing others), mendengarkan (listening), dan mau terlibat/mendampingi (being involved) and in they have been practicing SL as in line with the understanding. These understanding and practice have been confirmed by the findings from the questionnaire that 3 out of 6 dimensions of SLBS that have been understood and implemented well, specifically: Voluntary Subordination, Covenantal Relationship, and Transforming Influence.